Generation Z: A comparative study of the expectations of Gen Z and the perception of employers - Susanne Böhlich; Richard Axmann (IUBH Internationale Hochschule, 2020)
Employers currently encounter more and more members of Generation Z - who finished their school as well as university education - without knowing exactly what this generation wishes and needs. This paper verifies current assumptions about Generation Z with a quantitative study in Germany, consisting of two parts. As a first step, members of Generation Z (n = 103) were queried upon their work attitudes while in a second step, company representatives (n = 48) were asked about their assumptions on the adolescents' preferences. Thus, not only conclusions on young adults could be drawn, but also on the (lack of) knowledge about Generation Z of their employers. The prior assumption that the young generation would be difficult to employ inter alia due to their refusal of a work-life blending, lacking career orientation, and inability to take feedback could not be supported. In fact, Generation Z seems to be committed as well as motivated to work for their professional success. Employers showed a decent understanding of their young employees, though there seem to be a couple of misapprehensions.
Keywords: M12; M50; 650; Generation Z; work attitudes; desired workplace design; leadership; feedback culture